Blood corticosterone measurement in rat model of type 1 diabetes mellitus - Kadzharyan, E. V.; Grekova, T. A.; Каджарян, Єлизавета Віталіївна; Грекова, Тетяна Анатоліївна (Запорізький державний медичний університет, 2019)
It has been known that diabetes mellitus (DM) is accompanied by increased glucocorticoid secretion secondary to hyperglycemia which is associated with an extensive list of disease complications. Levels of cortisol in humans, or corticosterone in rats, are usually measured as transitory biomarkers of stress in blood or saliva.